Mental health, self-efficacy and university adaptation to the COVID-19 pandemic - Gonçalves Correia Zanini, Marta Regina (2022)
This mixed study evaluated changes and stability in health indicators (depression, anxiety, stress, alcohol consumption and amount of hours of sleep) and the belief in academic self-efficacy of Brazilian university students, before and during the COVID-19 pandemic. The first step, quantitative and longitudinal, investigated 20 students (average age=20.8 years; SD=3.4) in the period of 2019 and 2020, suggesting the maintenance of mental health indicators and the reduction of alcohol consumption and self-efficacy. In the second, qualitative stage, interviews during the quarantine revealed processes of personal and academic adaptation, in addition to concerns about mental health in the face of the pandemic. Institutional responses by universities to these ongoing challenges are recommended, as opposed to an individual analytical perspective.